Development Status of Compressor Technology for Medium and Large Capacity Industrial High-Temperature Heat Pumps - Ma Kai; Chen Wenqing; Li Dantong; He Zhilong; Xing Ziwen (Zhileng xuebao)
Heat pump technology is an energy-saving solution that could potentially combat global warming and reduce carbon emissions. Industrial heat pumps recover waste heat from the heating process to heat water or air, thereby reducing electricity consumption and carbon emissions. Industrial heat pumps are energy-saving, environmentally friendly, and provide stable heating. They have been widely used at all stages of production and life. This study analyzes the compressor types and characteristics of domestic and international high-temperature heat pumps (HTHP) that recover industrial waste heat and analyzes their application and technical status with a focus on twin-screw and centrifugal compressors. Twin-screw heat pump compressors should adopt an open structure when the evaporation temperature is high, and high-speed and oil-free design can be used when the condensation temperature is high. In addition, centrifugal heat pump compressors should prioritize highly efficient impellers, high-temperature-resistant motors, and oil-free lubricated bearings. Screw steam compressors need to solve the problems of rotor thermal deformation and shaft seal, and target for large temperature lifts.